Production of Talisia esculenta seedlings under irrigation with saline water in substrate with hydrogel - Bezerra, Francisco Thiago Coelho; Bezerra, Marlene Alexandrina Ferreira; Pereira, Walter Esfrain; Oliveira, Carlos Jardel Andrade de; Souza, Gleyse Lopes Fernandes de; Nascimento, Ana Paula Pereira do (Comunicata Scientiae, 2022)
Salinity is one of the factors that compromise the formation of seedlings, so it is necessary to associate measures that mitigate its effects. The objective of this study was to evaluate the effects of irrigation frequencies, water salinity, polymer and container volume on the growth and quality of Talisia esculenta (A. St.-Hil.)Radlk seedlings. The treatments were obtained from the combination of polymer concentrations (0.0; 0.2; 0.6; 1.0 and 1.2 g dm-3), electrical conductivities of water (0.3; 1.1; 2.7; 4.3 and 5.0 dS m-1) and irrigation frequencies (daily and alternate) plus two additional treatments to evaluate container volume. The growth and quality of seedlings were analyzed at 100 days after sowing. Reduction in irrigation frequency from daily to alternate days reduced the growth, biomass accumulation, and quality of the seedlings. Overall, salinity hampered the formation of the seedlings while the polymer had positive effects. T. esculenta seedlings are considered to be sensitive to salinity and should be irrigated using water with conductivity of up to 0.7 dS m-1 at a daily frequency of application. The polymer can be incorporated up to 1.2 g dm-3 and containers with higher volumetric capacity (0.75 vs 1.30 dm3) are indicated for the production of T. esculenta seedlings.